Influence of initial surface roughness on the deposition and adhesion of electroless Ni-P plating on 6H-SiC substrate - Hossein Ahmadian; Tianfeng Zhou; Weijia Guo; Qian Yu; A.M. Sadoun; A. Fathy; Yang Xuanzhe; M. Elmahdy (Results in Engineering)
The aim of this study is to examine the effect of substrate surface roughness on the deposition and adhesion properties of electroless Nickel-Phosphorus (Ni-P) plating on 6H-SiC substrates, which is a typical mold material for Precision Glass Molding (PGM). This research investigated the impact of surface roughness at different levels. These levels range from polished surfaces with Ra∼58 nm to non-polished surfaces with Ra∼813 nm, affecting both the electroless Ni-P plating process and the quality of the resulting layers. The study reveals that the initial roughness of the substrate significantly influences the final surface profile of electroless Ni-P plating. This is evidenced by the highest roughness of approximately Ra∼1.32 µm observed on the most uneven substrate. Conversely, substrate characterized by an initial roughness of Ra∼160 nm has a reduced post-plating roughness of Ra∼583 nm and contribute to the smoothness of surface. While the observed surface morphology indicates a decrease in the deposition rates. Additionally, the Rockwell C indentation tests indicate that substrates characterized by lower roughness are susceptible to adhesion difficulties, particularly in the form of peeling at the plating-substrate interface.